Edge effects on the orchid-bee fauna (Hymenoptera: Apidae) at a large remnant of Atlantic Rain Forest in southeastern Brazil - Nemésio,André (2006)
Male orchid bees were sampled with chemical baits monthly from July 1999 to April 2000 at six sites situated at different distances from the forest edge (0 to 4,000 m) at Parque Estadual do Rio Doce, the largest remnant of Atlantic Forest in the state of Minas Gerais, southeastern Brazil. The main goal of this study was to assess the abundance, richness, and the community structure of the orchid-bee fauna at different distances from the edge. In all, 1,183 males from 20 species were collected. Only minor and insignificant variation in richness and abundance were observed among the sites. Two dominant species, Euglossa analis Westwood (Hymenoptera: Apidae) and Eulaema cingulata (Fabricius) (Hymenoptera: Apidae), showed strongly opposing habitat associations: while males of the former were most collected in the interior of the forest, the latter was most found at or close to the edge. The responses of individual species, such as these, and not composite measures of richness and abundance, are more informative regarding forest integrity and edge effects.